An automated management system for the community health service in China. Issue 4 (1st December 2017) - Hu, Hongpu; Zhang, Yue; Liu, Hongyan; Wang, Bingqian; Wan, Yanli
Abstract : Objective: To explore a useful tool for health administrative departments to manage the community health service (CHS). Methods: On the basis of existing health laws and regulations in China, we describe the design of an automated management system for the CHS with a supervision system and an evaluation system using computer technology and corresponding design software. Results: Four changes to the management of the CHS were made: repetitive work became automated, complicated work became simplified, nonregular services decreased, and obscure instructions became clear and specific. Conclusion: The automated management system will promote the development of CHS management.